Pyrolysis-GC-MS analysis of crude and heavy fuel oil asphaltenes for application in oil fingerprinting. Issue 1 (2nd January 2018) - Riley, Brenden J.; Lennard, Chris; Fuller, Stephen; Spikmans, Val
ABSTRACT: A Pyrolysis – Gas Chromatography – Mass Spectrometry (Py-GC-MS) method was developed for the analysis and profiling of crude and heavy fuel oil asphaltenes, for application in oil fingerprinting. Asphaltenes were precipitated from ten geographically different oils using n -pentane, and analysed by Py-GC-MS. Alkane profiles and sulphur/aromatic profiles were used to compare the oils, and to correctly differentiate oils from different geographical regions. Py-GC-MS could not differentiate a weathered oil sample and a fresh oil sample from the same source. The results of this study support the findings from a previously developed FTIR method for asphaltene profiling.